Manajemen Perpustakaan di Masa Pandemi Covid-19 - Aliviatus Sadiyah; Hinggil Permana (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
This research aims to analyze the role of library governance as an administrator to improve library services in schools during the pandemic. The library is an important part that needs to be developed in every school. Library management is the management of libraries based on theories and principles of management. One form of library management is development. Librarians and library managers during the pandemic were completely forced to change, and librarians had to adapt to the conditions of not being able to serve directly or face-to-face like them. The role of the library in the foreground is to create a cultural society that can still be felt. Currently librarians are trying to transform services that were previously carried out directly into Online services such as fairy tales, seminars, workshops, application development, library accreditation, authorship and other activities, so that the role of library management can still be felt.